THE RELATIONSHIP BETWEEN SECONDARY EDUCATION STUDENTS’ DIGITAL ADDICTION LEVELS AND THEIR INQUIRY SKILLS - Ayla YILDIZ (Istraživanja u Pedagogiji, 2021)
The aim of this study is to determine the relationship between high school students’ digital addiction levels and their inquiry skills. The sample of the study consists of 319 9th, 10th, 11th, and 12th grade high school students chosen by random sampling. Of these students studying in Sivas province schools of Turkey, two are Anatolian High School, and one is an Anatolian Imam Hatip (Religious) High School. 190 of the students are girls (59.6%), and 129 are boys (40.4%). Data were collected through the “Digital Addiction Scale (DAS)” developed by Dilci (2019) and the “Inquiry Skills Scale (ISS)” developed by Aldan Karademir and Saracaloglu (2013). In analyzing the data, the arithmetic mean and standard deviation values of the scores obtained from the scales were found, and Pearson’s correlation analysis and simple linear regression analysis tests were used. The study detected negative significant relationships, albeit low, between the DAS sub-dimensions of deprivation, impulsivity, underperformance, low self-perception, and social isolation and all the sub-dimensions of ISS (i.e. acquiring knowledge, controlling knowledge, and self-confidence). There was also a low negative significant relationship between the overall DAS and ISS scores of the high school students. Finally, digital addiction levels were determined to explain 5% of the variance in the high school students’ inquiry skills.